Antibacterial, Antioxidant, Collagenase inhibition, Urease inhibition activities and Chemical composition of the Essential oil and extracts of Cinnamomum zeylanicum bark. - Pooja Bharti; Leena Seasotiya; Sheema Bai; Anupma Malik; Sunita Dalal (International Journal of Phytomedicine, 2013)
Significant biological activities of bacterial infection like antibacterial, antioxidant, urease and collagenase inhibitory activities of the essential oil and various extracts of Cinnamomum zeylanicum were determined. The in vitro antibacterial activity against nine epidermal bacteria and 11 MRSA isolates was conducted. The essential oil of C. zeylanicum exhibited the activity against all bacteria with the Minimum Inhibitory Concentration values (MIC) ranging from 0.15 to 2.5 µl. The extracts showed declined antibacterial activity. The scanning electron microscopic (SEM) studies demonstrated potential detrimental effect of the essential oil on the morphology of tested bacteria. Antioxidant activity of all the samples was also determined and 20% activity was observed in essential oil. Collagenase inhibitory potential was upto 25% and 30% in aqueous and methanol extracts respectively while upto 35% in essential oil. None of the samples showed urease inhibitory activity. The chemical composition of hydrodistilled essential oil of C. zeylanicum was also analysed by GC-MS. A total of 13 compounds representing 100% of the oil were identified. Therefore, due to different chemical components present in the cinnamon essential oil, further investigation concerned with studied activities of this essential oil to replace the medicines or as supplement in diseases, is recommended.